A review of solar-powered membrane distillation system : Concept design and development - Mohd Amirul Hilmi, Mohd Hanoin; Farah Najihah, Zainuddin; Nadzirah, Mohd Mokhtar (ISRES Publishing, 2022)
Rising freshwater demands and environmental pollution lead to the increase of renewable energy utilization for seawater desalination system. One of the rapidly advancing technology for seawater desalination is the membrane distillation (MD) that has the potential to be integrated with renewable energy-driven operating systems, usually solar energy. This configuration is well known as solar-powered membrane distillation (SPMD), which can solve freshwater scarcity without increasing electricity cost. Numerous researchers have examined the integration of solar energy and MD for eco-friendly water desalination. However, there is a lack of information regarding this integrated system, although the system was invented over four centuries ago. In this review, the SPMD system was discussed in terms of its concept design and development. The significant contributions of the latest development of the SPMD system towards renewable energy and desalination technology were highlighted. In addition, the future research outlook in the area of SPMD is further discussed.